2022
DOI: 10.1186/s12885-022-10302-2
|View full text |Cite
|
Sign up to set email alerts
|

CX3CL1 promotes cell sensitivity to ferroptosis and is associated with the tumor microenvironment in clear cell renal cell carcinoma

Abstract: Background An increasing number of studies have demonstrated that CX3CL1 is involved in the development of tumors and may thus be considered a new potential therapeutic target for them. However, the function of CX3CL1 in clear cell renal cell carcinoma (ccRCC) remains poorly defined. Methods The pan-cancer expression pattern and prognostic value of CX3CL1 were evaluated in this study. Moreover, the relationship of CX3CL1 expression with the tumor m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Some studies have indicated that reduced ACADSB expression predicts poor prognosis in ccRCC [88]. miRNA-4735-3p targeted SLC40A1 to facilitate ferroptosis in ccRCC [89], and CX3CL1 enhanced cell susceptibility to ferroptosis and was related to the tumor microenvironment [90]. Ferroptosis was weakened by succinate dehydrogenase’s functional deficit, which encouraged tumorigenesis and the growth of ccRCC [91].…”
Section: Ferroptosis and Kidney Diseasesmentioning
confidence: 99%
“…Some studies have indicated that reduced ACADSB expression predicts poor prognosis in ccRCC [88]. miRNA-4735-3p targeted SLC40A1 to facilitate ferroptosis in ccRCC [89], and CX3CL1 enhanced cell susceptibility to ferroptosis and was related to the tumor microenvironment [90]. Ferroptosis was weakened by succinate dehydrogenase’s functional deficit, which encouraged tumorigenesis and the growth of ccRCC [91].…”
Section: Ferroptosis and Kidney Diseasesmentioning
confidence: 99%
“… 193 ccRCC Methylation β-OHB - CX3CL1 overexpression inhibited tumor cell proliferation and metastasis and promoted tumor ferroptosis sensitivity in ccRCC.The expression of CX3CL1 in ccRCC is correlated with its DNA methylation level. 195 ccRCC Methylation SDH - Increased methylation and high SDH promoter mutation rates lead to deficiency of SDH, thereby promoting tumorigenesis through weakening of ferroptosis. 196 ALL Methylation FSP1 - The promoter of the gene coding for FSP1 is hypermethylated in ALL, silencing the expression of FSP1 and creating a selective dependency on GSH-centered anti-ferroptosis defenses.…”
Section: Epigenetic and Posttranslational Modifications Regulating Fe...mentioning
confidence: 99%
“…The expression of CX3CL1 is associated with its DNA methylation level in ccRCC. 195 Decreased expression of succinate dehydrogenase (SDH), which is responsible for oxidative phosphorylation (OXPHOS) and flux through the tricarboxylic acid (TCA) cycle, is correlated with ccRCC progression. SDH deficiency enhances tumorigenesis by inhibiting ferroptosis in ccRCC cells.…”
Section: Epigenetic and Posttranslational Modifications Regulating Fe...mentioning
confidence: 99%
“…DNA methylation of the Fsp1 promoter prevented NRF2 from binding to its promoter and inhibited transcription [20,123]. In addition, DNA methylation of many other genes has been reported to contribute to ferroptosis regulation [98,[124][125][126][127][128]. For example, embryonic lethal-abnormal vision-like protein 1 (ELAVL1), a well characterized RNA-binding protein that promotes target mRNA stability, has been found to bind to the 3'UTR of DNMT3B mRNA, thereby facilitating its expression during cerebral ischemia/ reperfusion (I/R) injury.…”
Section: Dna Methylation In Ferroptosismentioning
confidence: 99%